2014
DOI: 10.1111/1742-6723.12276
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the site for intercostal catheter insertion in the emergency department: Is clinical examination reliable?

Abstract: Emergency registrars and consultants sampled from a regional ED appeared unable to reliably identify the 4th or 5th ICS, as evidenced by marker position, in a heterogeneous patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The problem arises however, that these anatomical landmarks are poorly recalled . Further, even when recalled, the landmarks are poorly identified, even more so perhaps under the cognitive demands of trauma resuscitation . Failure to correctly site the incision for either thoracostomy or chest drain is recognised as a contributor to morbidity, including iatrogenic injuries because of the incision being too low (endangering diaphragm, liver or spleen) or too high (endangering axillary vessels) .…”
Section: Discussionmentioning
confidence: 99%
“…The problem arises however, that these anatomical landmarks are poorly recalled . Further, even when recalled, the landmarks are poorly identified, even more so perhaps under the cognitive demands of trauma resuscitation . Failure to correctly site the incision for either thoracostomy or chest drain is recognised as a contributor to morbidity, including iatrogenic injuries because of the incision being too low (endangering diaphragm, liver or spleen) or too high (endangering axillary vessels) .…”
Section: Discussionmentioning
confidence: 99%
“…The ipsilateral arm is abducted and externally rotated as much as possible, with the patient's hand placed behind their head and restrained there. Textbooks and conventional teaching often refer to the Triangle of Safety for placement. Unfortunately, it is alarmingly common for the ICC to be placed too low in the chest . A thoracostomy incision should be at a level superior to the nipple line, in the axilla.…”
Section: What Is the Optimal Patient Position And Insertion Site For mentioning
confidence: 99%
“…Unfortunately, it is alarmingly common for the ICC to be placed too low in the chest. 3 A thoracostomy incision should be at a level superior to the nipple line, in the axilla. A good guide is the inferior margin of the axillary hairline -in most patients the correct placement will be one finger breadth below this.…”
mentioning
confidence: 99%
“…Another study had physicians placing a radiopaque marker on a patient’s chest wall over the 4th or 5th ICS prior to the patient getting a chest X-ray. This study demonstrated that physicians placed the marker correctly only 36.2% of the time [ 13 ]. In both of the aforementioned studies, the most common mistake made by the trainees was placing the marker for thoracostomy insertion too low [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%